Hanif Kureishi writing the self : a biography - Ranasinha, Ruvani (Manchester University Press, 2023)
" Original, bold and always funny, Hanif Kureishi is one of Britain's most popular, provocative and versatile writers. Born in Bromley in 1954 to an Indian father and white British mother, Kureishi's life is intimately bound up with the history of immigration and social change in Britain. This is the story of how a mixed-raced child of empire who attended the local comprehensive school found success with a remarkable series of novels and screenplays, including My Beautiful Laundrette and The Buddha of Suburbia, Intimacy, Venus and Le Week-End. The book also illuminates a larger story, not only of the artist as a young man, but of the recasting of Britain in the aftermath of decolonisation. Drawing on journals, letters and manuscripts from Kureishi's unexplored archive, recently acquired by the British Library, and informed by interviews with his family, friends and collaborators, as well with the writer himself, Ruvani Ranasinha sheds new light on how his life animates his work. This first biography offers a vivid portrait of a major talent who has inspired a new generation of writers."